Local Wisdom-Oriented Differentiation Strategies in Increasing the Competitiveness of Tourism Destinations: Evidence on Derawan Island Tourism - Saida Zainurossalamia ZA; Robiansyah Robiansyah; Syarifah Hudayah; Anggi Oktawiranti; Gusti Noorlitaria Achmad; Denis Ushakov (Yayasan Keluarga Guru Mandiri, 2025)
The tourism industry in Indonesia is faced with various challenges in facing the dynamics of competition while still paying attention to sustainability, especially amidst the government's efforts to develop new super-priority destinations close to the National Capital (IKN) in East Kalimantan, namely Derawan Island, Berau Regency. This study aims to analyze the effectiveness of local wisdom-based differentiation strategies in increasing the competitiveness of Derawan Island tourist destinations. The research method uses a mixed method. The population in this study were tourists at Derawan Island tourist attractions, where the local government, destination managers, business actors, and local communities became the primary informants, and tourists became informants. Quantitative sampling was carried out using purposive sampling of 80 people. Data was collected through in-depth interviews and surveys and analyzed using thematic and inferential statistics. The study results showed that local wisdom-based differentiation strategies significantly and positively affected Derawan Island's competitiveness. This can support the development of marketing strategies oriented towards local wisdom to increase the attractiveness of tourist destinations and create sustainable added value. There needs to be synergy from all stakeholders in maintaining cultural authenticity while increasing tourist appeal.